(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Hypertension is a worldwide health problem and one of the preventable cause of heart disease and stroke. Uncontrolledhypertension can result in a myocardial infarction, left ventricular hypertrophy, and ultimately heart failure. During oxidative stressfulcondition like hypertension, Vitamin C an important antioxidant, that is effective in trapping oxygen-derived free radicals and lowersthe blood pressure.Objectives: To assess the efficacy and safety of supplementing vitamin C to telmisartan as a treatment in mild to moderate hypertensionpatients to reduce blood pressure.Materials And Methods: An open label, randomised, prospective study, participants were enrolled in one of two groups. A total of 110participants were randomized into 2 groups in which group 1 has 55 participants who received Tab.Vitamin C 500mg OD along withTab.Telmisartan 40 mg OD and the next 55 participants were into group 2 who received only Tab.Telmisartan 40 mg OD. Theparticipants were followed for 16 weeks and they were asked to visit us at week 1, week 9, and week 16 during which their bloodpressures were monitored and noted.Results: In this study, the average baseline Systolic blood pressure (SBP) was 154.36 mm Hg in group - 1 (Tab.Vitamin C withTab.Telmisartan) and 152.11 mm Hg was in group 2 (Tab.Telmisartan), and the Diastolic blood pressure (DBP) was approximately94.36 mm Hg - group 1 and 93.67mm Hg - group 2. During the last visit i.e.,16th week, the average SBP decreased significantly ingroup 1 (132.98 mm Hg) than group 2 (144.33 mm Hg) and the DBP showed significant reduction in group 1(75.93mm Hg) than group2 (85mm Hg).Conclusion: Vitamin C when it is given as an add on therapy to telmisartan it shows significant reduction in blood pressure.